Hydration Heat of Nonshrinkage Concrete in Large-Diameter CFST Arch Ribs Cured at Low Temperatures - Tuo Shi; Nianchun Deng; Dong Pan; Shi Wang (Advances in Civil Engineering)
To study the construction of concrete-filled steel tubular (CFST) arch bridges in Tibet, China, the hydration-temperature field of nonshrinkage concrete in large-diameter CFST arch ribs was evaluated in a temperature-testing box to simulate a low-temperature environment. A finite element simulation was then conducted to replicate the experimental results. Finally, an improved formula with the parameters related to the diameter, the position, and the retarding time of concrete for predicting the hydration heat generated by non-shrinkage concrete in large-diameter CFST arch ribs cured at low temperatures was proposed. The formula results were shown to be consistent with the experimental results for low-temperature conditions and large diameters. This research method can be extended to predict the hydration heat at all locations in different-diameter CFSTs with different concrete mixes cured at various temperatures.